Efficacy and safety of Cadonilimab plus anlotinib in small cell lung cancer with brain metastases - Hai-Zhen Yi; Wei Lv; Jin-Jing Chen; Zhan Lin (Frontiers in Oncology)
PurposeThis study aimed to evaluate the efficiency and safety of Cadonilimab and Anlotinib pairing in individuals diagnosed with small cell lung cancer (SCLC) and brain metastases (BMs).MethodsA review was performed on individuals who were diagnosed with small cell lung cancer (SCLC) and had central nervous system (CNS) metastases confirmed via magnetic resonance imaging (MRI) of the brain.We assessed the treatment response of Cadonilimab plus Anlotinib using Response Evaluation Criteria in Solid Tumors version 1.1 (RECIST 1.1) and Response assessment in neuro-oncology brain metastases (RANO-BM) for evaluating solid tumors and neuro-oncology brain metastases, respectively.The patients’ prognosis was determined using Kaplan-Meier analysis and Cox regression analysis.FindingsThe study initially included 46 patients diagnosed with SCLC who presented with brain metastases (BMs). According to the RANO-BM criteria, intracranial lesions showed an objective response rate (ORR) of 41.3%. The median overall survival (OS) was observed to be 19.3 months (95% CI, 17.4-21.1 months). Multivariate Cox regression analysis showed that having a PD1 level below 50% (HR=4.83, P <0.001) or having two or more metastatic organs (HR = 2.71, P = 0.036) were independent factors that positively predicted overall survival of all the patients, 86.9% experienced treatment-related adverse events (TRAEs) associated with the treatment, while 17.4% reported severe TRAEs of grade3-4.ImplicationsAccording to our results, the combination of Cadonilimab and Anlotinib appears to be a promising treatment option for SCLC patients with brain metastases.